METHODS AND APPARATUSES FOR CONDITIONAL HANDOVER IN NON-TERRESTRIAL NETWORK - YAN, Le; DAI, Mingzeng; WANG, Haiming; WU, Lianhai; XU, Min (2025)
Disclosed are methods and apparatuses for conditional handover in a non-terrestrial network (NTN). An embodiment of the subject application provides a user equipment (UE). The UE includes a processor and a wireless transceiver coupled to the processor. The processor is configured to: receive, with the wireless transceiver, at least a conditional handover (CHO) configuration and a CHO execution condition for a target cell, wherein the CHO execution condition includes: a time-based event and at least one measurement-based event, or a location-based event and at least one measurement-based event; and evaluate whether the CHO execution condition is fulfilled.